PENGARUH PENDAPATAN MARGIN MURABAHAH TERHADAP LABA BERSIH PADA BANK SYARIAH di INDONESIA - Nabila, Nauva Khansa (Universitas Nusantara PGRI Kediri, 2020)
This study was made to determine the effect of murabahah margin income on net income. The variable used in this study murabaha margin income, and net profit. This research was made using quantitative methods with an associative approach. The population in this study is the 2017-2019 Sharia Commercial Bank financial statements with the sample used as many as 36 samples. In this study data collection techniques using secondary data. Analysis of the data used is the classic assumption test, multiple linear analysis, and hypothesis testing. The results of this study indicate that murabahah margin income has a significance value of 0.041 <0.05, which means it has a partial effect on net income. And the results of the determination coefficient test showed R = 0.786, with the results of the determination coefficient value of 61.77796 which means murabahah margin income does not have a significant effect on net income.